Modeling noncontact atomic force microscopy resolution on corrugated surfaces - Burson, Kristen M.; Yamamoto, Mahito; Cullen, William G. (Beilstein Journal of Nanotechnology, 2012)
Key developments in NC-AFM have generally involved atomically flat crystalline surfaces. However, many surfaces of technological interest are not atomically flat. We discuss the experimental difficulties in obtaining high-resolution images of rough surfaces, with amorphous SiO2 as a specific case. We develop a quasi-1-D minimal model for noncontact atomic force microscopy, based on van der Waals interactions between a spherical tip and the surface, explicitly accounting for the corrugated substrate (modeled as a sinusoid). The model results show an attenuation of the topographic contours by ~30% for tip distances within 5 Å of the surface. Results also indicate a deviation from the Hamaker force law for a sphere interacting with a flat surface.
Keywords: graphene; model; noncontact atomic force microscopy; SiO2; van der Waals